El país narrado de Manuel Ancízar. Análisis de la estética costumbrista en Peregrinación de Alpha y su conexión con el proyecto de la Comisión Corográfica (Colombia, 1850-1851). (2021)
Manuel Ancízar wrote a series of articles by the time he joined the Chorographic Commission project along the national territory of Colombia in the Nineteen century. Such articles were serialized in El Neogranadino Newspaper, and later published in a collection called The Pilgrimage of “Alpha”. As a whole, those written pieces were supposed to be, not only a description of the provinces of Nueva Granada, but a narrative construction that included descriptions of territory, weather, crops, economy basis, people, manners, customs, education facilities, religion and politics influences. In concrete, Manuel Ancízar built a hybrid relate to integrate the scientific data about the provinces collected by all the members of the Chorographic Commission but, far from being an unappealing report, the resulting croniques managed to captivate common readers as they were written under the coordinates of the costumbrism aesthetic. On this paper it is analysed the literary form and content of “Peregrinación” de “Alpha” in both its inner-textual dimensions and the social environment that surrounded its first publication.